Development and Implementation of a Virtual Environment in the Huancavelica-Based Metaverse for the Treatment of Psychoprophylaxis in Pregnant Women - Perez Mamani, Alberth (2025)
The neonatal mortality has remained one of the main problems, being even more recurrent in regions with vulnerable populations or high poverty rates, where most of these cases die due to inadequate, preventable care. This study seeks to explore the use of the metaverse to improve prenatal psychoprophylaxis by providing an immersive virtual environment that facilitates remote interaction between specialist physicians and pregnant women. A free methodology was used, ranging from planning and avatar selection to implementation and launch. The results demonstrated that the metaverse is a viable environment to improve accessibility, interaction, and prenatal care. In conclusion, this innovative approach could make prenatal care more interactive.